Participatory evaluation of community actions as a learning methodology for personal and community empowerment: case studies and empowerment processes - Xavier Úcar Martínez; Pilar Heras; Pere Soler (Sociedad Iberoamericana de Pedagogía Social, 2014)
Introduction: Participatory evaluation (PE) is a hybrid methodology that can be used simultaneously to investigate and act in groups and communities. It can generate new knowledge about reality, but it also allows changes in the participants and their sociocultural context. This research project, developed over three years, aims to find out whether PE processes are useful and appropriate to evaluate community actions and to generate learning that contribute to the empowerment of people who develop them. Method: The methodological structure of the research process design Participatory Evaluation processes that are applied in three selected communities-cases, over one year. The steering groups in each case evaluated four dimensions of Community Development Plans: context, evolution, performance and results, using different techniques and group dynamics. Throughout this process, participants identify the acquired knowledge and this is linked to indicators of empowerment, using questionnaires, content analysis and semi-structured interviews. Results: The development PE process in the three analyzed cases confirmed that PE is a useful strategy to assess participatory community actions of a territory; to report them to the people of the community; and to make shared decisions, about initiatives in order to improve community actions. The obtained results also verify that, throughout PE, there has been learning in the participants. Conclusions: The involvement of community members in the evaluation makes it more useful, fairer and more valid, but also a fourth positive consequence of PE is empowerment. From the process and the results of these cases of Participatory Evaluation, we consider that community EP is social transformation.